Inherited Depositional Topography Control on Shelf-Margin Oversteepening, Readjustment, and Coarse-Grained Sediment Delivery to Deep Water, Magallanes Basin, Chile - Bauer, Dustin B.; Hubbard, Stephen M.; Covault, Jacob A.; Romans, Brian W. (Frontiers in Earth Science, 2020)
A basin-margin depositional system is the stratigraphic product of terrigenous sediment delivery to the ocean, comprising a flat to low-gradient shelf, or topset, which transitions to a steeper deep-water slope, and, ultimately, a relatively flat basin floor. Erosional and depositional processes across these physiographic domains approximate a clinoform in the stratigraphic record. The shelf margin is a critical environment for terrigenous sediment dispersal because it links the shelf to deep water, and the coarse-grained deposits of associated strata are important subsurface reservoirs. Here, we characterize the shelf-margin and upper slope stratigraphy of the outcropping Upper Cretaceous Tres Pasos and Dorotea formations, Magallanes Basin, southern Chile. The Late Cretaceous Magallanes retroarc foreland basin was an elongate trough oriented parallel to the southern Andean arc and fold-and-thrust belt. The Tres Pasos and Dorotea formations record southward (basin axial) progradation of a high-relief shelf and slope system (>1000 m paleo-water depth) represented by a stratigraphic succession up to 3 km thick that is exposed for tens of kilometers along depositional dip. The character and distribution of deposits that define shelf margins contain evidence for a variety of processes related to deposition, erosion, sediment bypass, and mass wasting. The overall architecture of the Magallanes Basin strata is indicative of a graded basin-margin system interrupted by periods of slope oversteepening and development of out-of-grade conditions. These punctuated periods are recognized by sedimentological evidence for enhanced sediment bypass of the upper slope, and thick submarine fan successions in more distal segments. Development of oversteepened depositional topography is particularly significant as it instigated the only two major periods of coarse-grained sediment delivery to deep water over ~8 Myr during the Campanian. The controls on sediment dispersal beyond the shelf margin are commonly discussed in terms of allogenic forcings, such as tectonics, climate, and receiving-basin geometry, as well as autogenic behavior, such as delta-lobe switching. However, inherited depositional topography does not clearly fit within an allogenic/autogenic dichotomy. Depositional topography inherited from basin-margin evolution influences the position of subsequent shelf margins, which promote coarse-grained sediment delivery to deep water.